PENGARUH HIDROTERMAL SEKAM PADI TERHADAP PRODUKSI BIOMETANA PADA AGS – SBR - Muhammad Reza Huseini; Nur Afifah; Wiwit Ayuningtyas Pratiwi (JURNAL KONVERSI, 2018)
The quantity of waste water from domestic and industrial activities has increased significantly over the year, equivalent with increasing production of sewage sludge (schmid, 2000). Sewage Sludge high contents of organic and derivatives (Ammonia Nitrogen (NH4+), Nitrate, Nitrite) and also levels of COD and BOD that exceed the quality standard. Anaerobic Granular Sludge – Sequence Batch Reactor (AGS-SBR) is a kind of Waste Water Treatment Plant (WWTP) which combine the biological treatment, aeration and sedimentation process into one reactor. AGS-SBR is able to reduce organic pollutants, COD and BOD above 60%. In cycle process of AGS-SBR is also able to optimize methanogenesis process in the growth of microorganisms to convert biomass (sewage sludge) became biomethane. Hydrothermal of rice husk is able to produce substrate that serves as a growth medium for microorganisms. The addition of rice husk (SP) and hydrothermal rice husks (SPT) can inffluence the biomethane production from sewage sludge with variation of hydrothermal temperature of rice husk 110oC and 175oC. The results of this study obtained the average of biomethane production is 0,0458 with the highest content is 0,219 on SPT 110 and the average of biomethane production on SPT 175 is 0,0483 with the highest content is 0,223